THE EFFECT OF BILINGUAL DICTIONARY USE ON THE STUDENTS’ NARRATIVE WRITING - M. Syahid (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura)
The objective of this study is to investigate the effect of bilingual dictionary use on the students’ narrative writing. The method is true experimental method by conductingboth pre-test and post-test. The instrument of this researchwas test. Two classes were chosen, they are class VIII B as the experimental group and class VIII C as the control group. The experimental group didthe writing process by using bilingual dictionary, while the control group did the writing process without bilingual dictionary. The result showed that bilingual dictionary provided the significant different effect to the students’ narrative writing results. Both the mean scores of the experimental group were higher than the control group andthe t-values (t0)were also higher than the t table (tt)in level 0.05.